Students awareness on consumer’s right: a case study at Mara University of Technology, City Campus Melaka - Omar, Muhamad Anas (2008)
The study was conducted on 96 respondents comprising 48 male’s students and 48 students in Universiti Teknologi Mara Melaka City Campus (UiTM KBM) to ascertain awareness level among both categories on their consumer rights. It indicates that majority of students is highly aware about the consumer basic and general knowledge. Male respondents have partial awareness to the existence of legal laws and the Consumers Tribunal same as female respondents that have high level of awareness. Both male and female respondents have a partial awareness of consumer organization. The level awareness between males and females showed that there is no significant difference. Overall, the study showed that UiTM City Campus Melaka students have a reasonably high level of awareness on their consumer rights.